The politics of suburbia: Israel's settlement policy and the production of space in the metropolitan area of Jerusalem - Allegra, M. (2014)
Israel's settlement policy in the West Bank represents a crucial issue in the Israeli–Palestinian conflict. Through the examination of a single case study—the planning history of the Jewish settlement of Ma’ale Adummim, located in the eastern periphery of the city—the paper addresses the complex nexus between planning and state-building practices; building on Henri Lefebvre’s theory of space, he offers an account of the role of Israel’s settlement policy in the transformation of the material, symbolic, and political landscape of the metropolitan area of Jerusalem. My main argument is that the observation of the development of large suburban communities in the metropolitan area—a blind spot both in media and in academic discourse—is crucial for our understanding of the settlement policy as a whole, and its impact on Israeli–Palestinian relations.